Layanan Konseling Individu Dengan Teknik Cognitive Behavioral Therapy Untuk Mengatasi Perilaku Bullying Remaja Di Desa Taja Indah Kabupaten Banyuasin Penerapan Konseling - Mentari, Mas; Razzaq, Abdur; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Individual counseling services using cognitive behavioral therapy techniques to overcome adolescent bullying behavior in Taja Indah Village, Banyuasin Regency. The aim of this research is to find out how individual counseling services use CBT techniques as therapy to control adolescent bullying behavior. The approach needed in this research is to take advantage of a qualitative approach through descriptive research methods. The results of this study are a description of the behavior of adolescents, namely speaking harshly and belittling other people. Individual counseling with CBT techniques is known to master adolescent bullying behavior by going through several stages, namely stage one, second, third. The story of adolescent bullying behavior has changed where it is not rude to say harsh words anymore and does not belittle other people's direct application to teenagers who do bullying with several stages.